Acculturation of Islam with Local Culture in Various Regions: A Case Study of the Begawi Customary Tradition in Lampung - Eni Hidayati; Dwi Ratnasari; Baha Shofa Mijdal (AN NUR: Jurnal Studi Islam, 2025)
This study aims to examine the process of Islamic acculturation with local culture in the Indonesian archipelago through a case study of the Begawi Adat Pepadun tradition in Lampung. The research is grounded in the understanding that local traditions in Indonesia are often perceived as contradictory to Islamic teachings, whereas, historically, both have coexisted and interacted dynamically. This research employs a qualitative approach using library research methods, reviewing academic sources such as books, journal articles, and cultural documents. Data were analyzed using content analysis to identify Islamic values integrated within the Begawi customary system. The results reveal that Begawi Adat represents a harmonious form of acculturation between Islam and local culture. Islamic values such as monotheism (tawhid), brotherhood (ukhuwah), deliberation (syura), moderation (wasathiyyah), and noble character (akhlaq al-karimah) are embedded in various stages of the ceremony, encompassing spiritual, social, moral, and aesthetic dimensions. The tradition serves not merely as a cultural event but as a medium for the internalization of Islamic teachings within the community. In conclusion, Begawi Adat Pepadun embodies the essence of Islam Nusantara peaceful, adaptive, and contextual while standing as a religious and cultural heritage that strengthens Islamic identity and preserves local wisdom in the modern era.